Prognostic factors for the loss of molars – an 18‐years retrospective cohort study. (26th October 2015) - Graetz, Christian; Schützhold, Svenja; Plaumann, Anna; Kahl, Maren; Springer, Claudia; Sälzer, Sonja; Holtfreter, Birte; Kocher, Thomas; Dörfer, Christof E.; Schwendicke, Falk
Abstract: Aim: The aim of this study was to identify long‐term prognostic factors for the loss of molars with different degrees of furcation involvement (FI) during supportive periodontal therapy (SPT). Methods: Three hundred and seventy‐nine compliant subjects with 2373 molars at baseline were retrospectively assessed. After nonsurgical ( n  = 76) or surgical ( n  = 303) non‐regenerative active periodontal therapy (APT: T0–T1), patients remained under SPT (T1–T2) for 18.3 ± 5.5 (9–30.8) years. Association between tooth‐ and subject‐related factors with tooth loss was assessed using multilevel Cox regression‐analysis. Results: During APT 159 and during SPT 438 molars were extracted in 256 subjects, respectively, yielding an overall survival of 74.8% (T2). Survival probabilities after 15‐years of SPT were 92.4% for molars with FI‐0 compared to FI‐1 = 85.6%, FI‐2 = 74.9% and FI‐3 = 62.3%. The risk of molar loss was significantly increased for teeth with FI‐3 (hazard ratio: 2.39 [95% confidence interval: 1.54–3.70]), bone loss >50% (2.16 [1.36–3.42]), mobile teeth (2.07 [1.51–2.84]), maxillary molars (1.44 [1.12–1.85]) and endodontically treated teeth (1.89 [1.58–2.26]). For each mm of mean residual pocket probing depth, the hazard of tooth loss increased 1.89‐fold (1.58–2.26). On a subject level, for each year of age, HR was 1.03 (1.01–1.05). Conclusions: Furcation involvement, bone loss, tooth mobility, mean pocket depth and age strongly predicted tooth loss during SPT. Long‐term retention of periodontally compromised molars was possible via conservative non‐regenerative active and supportive therapy.